PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP KINERJA APARATUR PEMERINTAHAN NAGARI DALAM PENGELOLAAN KEUANGAN NAGARI - octavia malinda; Syamsir Syamsir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
The purpose of this study was to analyze the effect of internal control system on the performance of nagari apparatus in nagari financial management in Tanah Datar Regency. This study was a quantitative research with associative method. The population of this study was all nagari apparatus in Tanah Datar Regency, which numbered 600 people.Sample inthis study was consisted of 248 nagari apparatus determined with Slovin formula. Besides, samplein this study determined through multistage random sampling technique. Data in this study were collected through questionnaires with Likert scale measurement distributed to respondents. The data were then analyzed using multiple linear regression. The results of this study indicated that internal control system (in the planning, implementation, administration, reporting, and accountability stages, together and partially), had a significant effect on the performance of nagari apparatus in managing nagari financial in Tanah Datar Regency. So that it could be concluded that the internal control system of nagari apparatus had a significant effect on the performance of nagari apparatus in nagari financial management in Tanah Datar Regency.